Protein Abundance of Clinically Relevant Drug Transporters in The Human Kidneys - Oswald, Stefan; Müller, Janett; Neugebauer, Ute; Schröter, Rita; Herrmann, Edwin; Pavenstädt, Hermann; Ciarimboli, Giuliano (International journal of molecular sciences, 2019)
Renal drug transporters such as the organic cation transporters (OCTs), organic anion transporters (OATs) and multidrug resistance proteins (MRPs) play an important role in the tubular secretion of many drugs influencing their efficacy and safety. However, only little is known about the distinct protein abundance of these transporters in human kidneys, and about the impact of age and gender as potential factors of inter-subject variability in their expression and function. The aim of this study was to determine the protein abundance of MDR1, MRP1-4, BCRP, OAT1-3, OCT2-3, MATE1, PEPT1/2, and ORCTL2 by liquid chromatography-tandem mass spectrometry-based targeted proteomics in a set of 36 human cortex kidney samples (20 males, 16 females; median age 53 and 55 years, respectively). OAT1 and 3, OCT2 and ORCTL2 were found to be most abundant renal SLC transporters while MDR1, MRP1 and MRP4 were the dominating ABC transporters. Only the expression levels of MDR1 and ORCTL2 were significantly higher abundant in older donors. Moreover, we found several significant correlations between different transporters, which may indicate their functional interplay in renal vectorial transport processes. Our data may contribute to a better understanding of the molecular processes determining renal excretion of drugs.